Shuo fu : Xiang jiang gu shi yi yang jiang dao li = Methods of persuasion - Kolenda,Nick (Nanjing : Jiangsu Fenghuang Wenyi Chuban She, 2017)
Using principles from cognitive psychology, Nick Kolenda developed a unique way to subconsciously influence people's thoughts. He developed a 'mind reading' stage show depicting that phenomenon, and his demonstrations have been seen by over a million people across the globe. Methods of Persuasion reveals that secret for the first time. You'll learn how to use those principles to influence people's thoughts in your own life. Drawing from academic research in psychology, the entire book culminates a powerful 7-step persuasion process that follows the acronym, METHODS: Step 1: Mold Their Perception Step 2: Elicit Congruent Attitudes Step 3: Trigger Social Pressure Step 4: Habituate Your Message Step 5: Optimize Your Message Step 6: Drive Their Momentum Step 7: Sustain Their Compliance This book teaches you the psychology behind each step. You'll learn how to apply METHODS to your own life so that you can influence people's thoughts, emotions, and behavior in nearly any situation.
$1!JH'Ep'`7!Tk!BX'`P!5E(B:Methods of persuasion: how to use psychology to influence human behavior.s
In simplified Chinese script.
Keywords: Persuasion (Psychology); Influence (Psychology)